Integrasi Nilai dan Spiritualitas dalam Kurikulum Berbasis Cinta untuk Humanisasi Pembelajaran di Madrasah - Farihin, Farihin; Sholeh, Yatim; Khotimah, Isnol (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
The transformation of Islamic education in the digital era demands a balance between technological advancement and the spiritual development of learners. This study aims to analyze the meaning, relevance, and implementation of the Love-Based Curriculum within the madrasah context, which emphasizes compassion (rahmah), empathy, and the humanization of learning as the core of the educational process. Employing a qualitative approach with a case study design at MA Riyadlus Sholihin Kota Probolinggo, data were collected through interviews, observations, and document analysis. The findings reveal that the Love-Based Curriculum strengthens students’ spiritual and moral dimensions through reflective learning and the teacher’s role as murabbi (spiritual mentor). Although institutional support is relatively strong, limitations in teacher training and technological adaptation remain challenges. This research highlights the urgency of adopting a love-oriented paradigm in Islamic education as a solution to the moral crisis and dehumanization found in modern education.